2006
DOI: 10.1111/j.1440-1819.2006.01530.x
|View full text |Cite
|
Sign up to set email alerts
|

Recidivism among male subjects incarcerated for illicit drug use in Taiwan

Abstract: Illicit drug users are generally considered both patients and criminals in Taiwan. This study presents drug use behaviors and criminal recidivism of male subjects incarcerated for illicit drug use in Taiwan after detoxification at a detention center. This study also examined the relationship between drug use behaviors and subsequent recidivism. Charts and crime records of 794 male patients from the acute detoxification unit in a detention center in northern Taiwan were reviewed. These subjects were incarcerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 28 publications
(35 reference statements)
2
25
0
Order By: Relevance
“…However, the current study indicates that length of residency in the detoxification program was not associated with the stage of change, decisional balance, and self‐efficacy for illicit drug use. The reported recidivism rates during the 5‐year follow‐up after detoxification at detention centers in Taiwan were 64.7% for methamphetamine users and 80.1% for heroin users 5 . The study findings are similar to a study in China that found that the number of detoxification treatments was not associated with any decrease in drug practices or unprotected sex 37 .…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…However, the current study indicates that length of residency in the detoxification program was not associated with the stage of change, decisional balance, and self‐efficacy for illicit drug use. The reported recidivism rates during the 5‐year follow‐up after detoxification at detention centers in Taiwan were 64.7% for methamphetamine users and 80.1% for heroin users 5 . The study findings are similar to a study in China that found that the number of detoxification treatments was not associated with any decrease in drug practices or unprotected sex 37 .…”
Section: Discussionsupporting
confidence: 75%
“…Two 6-item scales measure the pros and cons of making a decision to use illicit drugs and condoms. Each item is ranked on a 5point Likert scale, ranging from extremely important (1) to not important (5). The reliability of the previous study has been reported for both pro and con items (Pros: alpha = .86; Cons: alpha = .87).…”
Section: Instrumentsmentioning
confidence: 96%
See 3 more Smart Citations